Crossover of the Hypothalamic Pituitary–Adrenal/Interrenal, –Thyroid, and –Gonadal Axes in Testicular Development - Castañeda Cortés, Diana C.; Langlois, Valerie S.; Fernandino, Juan I. (Frontiers in Endocrinology, 2014)
Besides the well-known function of thyroid hormones (THs) for regulating metabolism, it has recently been discovered that THs are also involved in testicular development in mammalian and non-mammalian species. THs, in combination with follicle stimulating hormone (FSH), lead to androgen synthesis in Denio rerio, which results in the onset of spermatogenesis in the testis, potentially relating the hypothalamic-pituitary-thyroid gland (HPT) to the hypothalamic-pituitary-gonadal (HPG) axes. Furthermore, studies in non-mammalian species have suggested that by stimulating the thyroid-stimulating hormone (TSH), THs can be induced by corticotropin-releasing hormone (CRH). This suggests that the hypothalamic-pituitary-adrenal/interrenal gland (HPA) axis might influence the HPT axis. Additionally, it was shown that hormones pertaining to both HPT and HPA could also influence the HPG endocrine axis. For example, high levels of androgens were observed in the testis in Odonthestes bonariensis during a period of stress-induced sex determination, which suggests that stress hormones influence the gonadal fate towards masculinization. Thus, this review highlights the hormonal interactions observed between the HPT, HPA and HPG axes using a comparative approach in order to better understand how these endocrine systems could interact with each other to influence the development of testes.